PENGARUH PELATIHAN KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN - HARTONO, SONY (Jurnal Ilmu Manajemen (JIM), 2016)
Along with the times and needs, the company or organization has a wide range of instruments to achieve its goals. The company also must give the maximum attention for the employees, good attention which have a direct bearing on efforts to increase the capabilities and skills of employees and the level of welfare. For it with their job training program and create non-physical working conditions should be able to improve employee performance. Sampling techniques in this study using sampling techniques saturated with 60 permanent employees at PT. Pegadaian (Persero) Regional Office of Surabaya. Data analysis techniques in this study using multiple linear regression analysis with SPSS 18.0. Results of the study explained that: 1) job training significant positive effect on employee performance, 2) non-physical work environment significant positive effect on employee performance, and 3) Job training and non-physical work environment simultaneously significant positive effect on employee performance. Keywords: Job Training, Work Environment Non-physical and employee performance